GEOLOGI DAN POTENSI BAHAN GALIAN DAERAH WASEGI, DISTRIK PRAFI KABUPATEN MANOKWARI, PROVINSI PAPUA BARAT: GEOLOGY AND POTENTIAL OF MINERAL MATERIALS IN WASEGI AREA, PRAFI DISTRICT, MANOKWARI REGENCY, WEST PAPUA PROVINCE - Hermina Haluk (JISTECH: Journal of Information Science and Technology, 2014)
Administratively the research area is in Wasegi and surrounding area which located in Prafi District, Manokwari Regency, West Papua Province, Indonesia. The research goal is to understand the geology of Wasegi as well as the minerals resources potential. The methods that used are geological mapping and petrography of the rock samples. The area consists of three geomorphology units; fluvial-land unit, ripples denudation mount unit, and parallels denudation mount unit, in the juvenile to mature stadia. The stratigraphy of the research area is start from the oldest to the youngest; Kemum Schist, Maruni Crystalline Limestone, Lembai Diorite Intrusion Unit, and Pebbles - Clay Sediment. The geological structure that developed in the research area is shear joint structures on Northwest to East Southeast direction at Kemum Schist and Lembai Diorite Intrusion Unit. The possible resources of the research area that could be developed are sedimentation materials such as diorite, pebbles, and sand for building materials as well as the river sedimentation that the locals used in search for gold.